Implementation of 26 Gy in five fractions over 1 week adjuvant radiotherapy for breast cancer: Prospective report of acute skin toxicity and consideration of resource implications. (February 2023) - Nugent, K.; Quinlan, E.; Cleary, S.; O'Driscoll, H.; Rohan, C.; Trousdell, J.; Williams, J.; Dunne, M.; McArdle, O; Duane, F.K.
Abstract: Purpose: In March 2020, a 1-week adjuvant breast radiotherapy schedule, 26 Gy in 5 fractions, was adopted to reduce the risk of COVID19 for staff and patients. This study quantifies acute toxicity rates and the effect on linac capacity. Materials and methods: This is a report of consecutive patients receiving ultrafractionated breast radiotherapy ( ± sequential boost) Mar–Aug 2020. Virtual consultations assessed acute skin toxicity during treatment and weeks 1, 2, 3 and 4 post treatment using CTCAE V5 scoring criteria. The number of linac minutes saved was estimated accounting for boost and DIBH use. Results: In total, 128/135 (95%) patients, including 31/33 boost patients, completed at least 3/5 assessments. 0/128 (0%) reported moist desquamation not confined to skin folds or minor bleeding (Grade 3), 41/128 (32%) reported brisk erythema, moist desquamation confined to skin folds or breast swelling (Grade 2), 62/128 (48%) reported faint erythema or dry desquamation (Grade 1) as their worst skin toxicity, with the remaining 20% reporting no skin toxicity. The highest prevalence of grade 2 toxicity occurred week 1 following treatment (20%), reducing to 3% by week 4. There was no difference in toxicity between those who received a boost versus not (p = 1.00). Delivering this schedule to 135 patients over six months saved 21, 300 linac minutes and 1485 hospital visits compared to a 3-week schedule. Conclusion: Rapidly implementing ultrahypofractionated breast radiotherapy is feasible and acute toxicity rates are acceptable even when followed by boost. Highlights: It is feasible and safe to rapidly implement ultrahypofractionated breast RT. 26 Gy in 5 fractions ( ± sequential boost) leads to G0-2 acute skin toxicity. G3 acute skin toxicity is usually not observed with ultrahypofractionated breast RT. Ultrahypofractionation does not lead to excess toxicity when breast volume is large. Ultrahypofractionation saved 6300 LINAC minutes over 6 months (135 patients).